2010
DOI: 10.1039/b915596a
|View full text |Cite
|
Sign up to set email alerts
|

Designed pneumatic valve actuators for controlled droplet breakup and generation

Abstract: The dynamic breakup of emulsion droplets was demonstrated in double-layered microfluidic devices equipped with designed pneumatic actuators. Uniform emulsion droplets, produced by shearing at a T-junction, were broken into smaller droplets when they passed downstream through constrictions formed by a pneumatically actuated valve in the upper control layer. The valve-assisted droplet breakup was significantly affected by the shape and layout of the control valves on the emulsion flow channel. Interestingly, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 56 publications
0
43
0
1
Order By: Relevance
“…Emulsion droplet size and distribution significantly influence its properties (Ambrosone et al 2004;Klink et al 2011;Whitby et al 2007;Urbina-Villalba et al 2003). It is well known that microfluidic devices are effective platforms for producing monodispersed microdroplets or microbubbles (Marmottant and Raven 2009;Choi et al 2010). Several studies have already characterized the preparation of monodispersed droplets in microfluidic devices with various configurations, including T-shape microchannels (Xu et al 2005(Xu et al , 2006, co-flowing pipes (Cramer et al 2004;Chu et al 2007), hydrodynamic flow-focusing microchannels (Wang et al 2007;Xu and Nakajima 2004) and geometrically mediated breakup microchannels (Jullien et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Emulsion droplet size and distribution significantly influence its properties (Ambrosone et al 2004;Klink et al 2011;Whitby et al 2007;Urbina-Villalba et al 2003). It is well known that microfluidic devices are effective platforms for producing monodispersed microdroplets or microbubbles (Marmottant and Raven 2009;Choi et al 2010). Several studies have already characterized the preparation of monodispersed droplets in microfluidic devices with various configurations, including T-shape microchannels (Xu et al 2005(Xu et al , 2006, co-flowing pipes (Cramer et al 2004;Chu et al 2007), hydrodynamic flow-focusing microchannels (Wang et al 2007;Xu and Nakajima 2004) and geometrically mediated breakup microchannels (Jullien et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…During recent years, the growing trend in microfluidic device facilitates reducing the dispersion scale of emulsions into microscale (Engl et al 2008;Teh et al 2008). Monodispersed microbubbles and microdroplets can be controllably prepared in microfluidic devices (Choi et al 2010;Marmottant and Raven 2009) and it has been proved that the microdispersed emulsion systems have good transport and reacting properties (Panic et al 2004;Xu et al 2008a). Using these properties, microfluidic devices can be applied to enhance chemical reactions (Razzaq et al 2009), prepare microsphere materials (Park et al 2009), synthesize nanoparticles (Sevonkaev and Matijevic 2009), provide biological analysis (Felbel et al 2008), develop fuel cells (Kjeang et al 2009), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed microfluidic systems for splitting one droplet into several daughter droplets and controlling the division ratio, by adjusting the flow resistances of microchannels (Link et al 2004;Menetrier-Deremble and Tabeling 2006). Also, a microfluidic system to actively control the division ratio has been proposed, by employing electrical (Link et al 2006) or thermal (Ting et al 2006) control, microvalve actuation (Choi et al 2010) or a bifurcating microchannel where the distribution ratio at the branch point was controlled by introducing a continuous phase into one of the two branch channels (Yamada et al 2008). As another example, Lao et al (2009) have reported on a microfluidic system to generate double emulsions, in which they obtained droplets incorporating up to ten inner daughter droplets generated by multistep droplet division.…”
Section: Introductionmentioning
confidence: 99%